Social Service Strategies in Dealing with the Phenomenon of Street Clown Beggars: A Case Study of Palembang City - Agrevina Novhelia; Isabella; Amaliatulwalidain (Universitas Muhammadiyah Palu, 2025)
This research aims to find out and understand the role of the Social Service in the Palembang City Street Clown Beggar Rehabilitation Program. The research method used is a descriptive qualitative approach with data collection techniques through in-depth interviews, observations, and documentation in several places such as the Palembang City Social Service, Simpang Polda, and Radial. Data analysis is carried out through data collection, data presentation, and verification and affirmation of conclusions. The results of the study show that the role of the Social Service in the Palembang City Street Clown Beggar Rehabilitation Program is not only collecting data on clown beggars, the Social Service also provides social direction and guidance to street clown beggars, this program also supports the success of the rehabilitation program. This rehabilitation program can also be supported by the community and other governments. The impact of this program can also raise awareness of street clown beggars for more viable life changes. Overall, this study can be concluded that the role of the Social Service in the Palembang City Street Clown Beggar Rehabilitation Program is not optimal, but the Social Service has done it in accordance with the SOPs, the main factor is not optimal because other government involvement has not been achieved to collaborate with the Palembang City Social Service, therefore this study suggests the need for cooperation and involvement with the government, The TNI, the National Police to strengthen the rehabilitation program so that the coordination is more effective.